Natural resources and capital structure - Sanna Kurronen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This paper examines the effect of natural resources on capital structure of the firm. Using an extensive dataset of listed firms in 70 countries, we show that firms operating in resource extraction industries have less debt and that that debt tends to have a longer maturity than that of other non-financial firms. Moreover, non-resource firms in resource-dependent countries are found to be less indebted than their counterparts in other countries. The results suggest that the very fact of a firm's location in a resource-dependent country may be an overlooked country-specific de-terminant of firm capital structure and that financial institutions in resource-dependent countries may play a role in exacerbating a nation's resource curse.
URN:NBN:fi:bof-201609021400
Keywords: G32; O13; Q32; 330